Dynamics of an Electromechanical Touchdown Bearing Mechanism - Janne E. Heikkinen; Henri Kauppila; Alexander Smirnov; Teemu Sillanpää; Eerik Sikanen; Jussi Sopanen, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Safety bearings are used as a back-up system for the rotor-systems that use active magnet bearings for supporting the rotor. When the control fails due to unexpected events, the rotor drops on the safety bearings that prevent further damages of the system. This paper presents dynamic studies of a novel electromechanical safety bearing solution. The parts of the studied system are modeled as rigid bodies and the purpose is the study the dynamics of a real system in means of simulation. The safety bearing mechanism is manufactured and measured in the laboratory environment. The study shows that the dynamic behavior of the system can be repeated using the simulation tools that combines mechanical description of the system, electromagnetics and control system. Also, the electromechanical safety bearing solution seems to be feasible from the dynamic perspective.